Application of the Joyfull Learning Model in Sociology Learning in High School - Taqwa, Ridhah; Erna Retna Safitri; Yulasteriyani (Universitas Pendidikan Ganesha, 2024)
Students have different backgrounds regarding social concepts so teachers have difficulty finding the right teaching method. Sociology learning is too theoretical and less relevant. As a result, the objectives of sociology learning cannot be achieved properly. Therefore, sociology learning needs to use a participatory and interesting approach so as to increase student motivation to learn. This research was conducted with a qualitative approach which aims to describe the implementation of the model fun learning in studying sociology at high schools in the cities of Pagar Alam and Muara Enim. The research method is participatory qualitative with teacher and student respondents. Data collection was carried out by observation, interviews and tests. Data analysis was carried out qualitatively, both in data presentation and interpretation. The research results show that sociology learning still uses conventional learning models with approaches teacher-centered. The learning method used is mostly lectures and minimal use of technology. As many as 74% of students expressed their readiness to accept more innovative, interactive and facilitative learning models that can provide fun and effective learning. The results of research on the implementation of learning using the joyful learning model show that there is an increase in knowledge of 36.5%, which means that the model joyful learning effectively used in sociology learning. The implications of this research are Schools need to support teacher training and provide adequate learning facilities to support the effective implementation of this model.